Effect of Torsional Loading in an Axisymmetric Micro-Isotropic, Micro-Elastic Solid - Rama, E. (Communications in Mathematics and Applications, 2021)
In this paper, an attempt is made to obtain the solution for the problem of torsional loading in an axisymmetric Micro-isotropic, Micro-elastic half-space under the action of an arbitrary load on its boundary. The components of displacement, microrotation, stress, couple stress and stress moment are obtained. These components are also obtained for a particular type of twist and represented graphically in the positive quadrant.